Análise das internações por condições sensíveis à Atenção Primária em hospital de referência regional, SP/Brasil - Nunes, Karina Rubia [UNESP] (2015)
The World Health Organization has formalized its commitment to primary health care (PHC) in the late 70s in the Alma Ata Conference, when the stressed as a key tool for meeting the goal Health for All. In Brazil, the Unified Health System (SUS) is a state policy and articulates the APS clinical actions of promotion, prevention, treatment and rehabilitation. These actions are based on the principles of universality, comprehensiveness and equity, and have as organizational principles Decentralisation, Regionalisation, Hierarchy and Social Participation. To the growing effort to improve the quality of PHC in the country, evaluative mechanisms have been widely used to improve services, the health actions and programs established at different levels of care. The evaluation of Admissions by Primary Care Sensitive Conditions (ICSAP) aims to identify gaps in access and quality of primary services offered to the population. The aim of this study is to analyze the ICSAP in a regional referral hospital in the period 2008-2012. The thesis consists of three studies, namely: a qualitative nature, literature integrative review; two quantitative, transversal and hospital-based. The main characteristics of APS associated with lower ICSAP rates were high coverage of the Family Health; health clinics located in urban areas; doctors in urban areas; rural clinics in areas with professional shortages; most doctor's length of stay in the Family Health team consultations in primary care in the previous year; consultations in primary care with quality and greater physician / inhabitant density; implementation of drug distribution program for over 65 years; financial incentives for primary care and funding for Indian Health Service. The hospital performed 49,476 hospitalizations in the 2008-2012 period, and of these only 7.43% were due Sensitive Conditions Primary. The three main causes of hospitalization were: Cerebrovascular diseases (27.3), Bacterial ...